2014
DOI: 10.3174/ajnr.a4099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spin-Echo and Gradient-Echo T1-Weighted and Spin-Echo T2-Weighted Images at 3T in Evaluating Term-Neonatal Myelination

Abstract: SUMMARY:A prior clinical report of 3T MR imaging in subsequently healthy very premature neonates imaged at term-equivalent age found that both gradient recalled-echo-T1WI and spin-echo-T2WI showed higher rates of myelinated structures, compared with spinecho-T1WI. The current study set out to assess those rates on the same sequences at 3T in term neonates and thus consisted of 16 term neonates with normal-appearing MR imaging findings who subsequently had normal findings at clinical follow-up. Two neuroradiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…T 1 W silent imaging is a gradient-echo inversion recovery sequence, and recent studies have shown that when compared with T 1 W SE images, 3T T 1 W gradient-echo images depict a higher degree of myelination in both full-term neonates and term-equivalent age infants. 14 , 15 The results of our study are similar to those earlier reports; moreover, the use of an inversion recovery technique might have improved the T 1 contrast in our study.…”
Section: Discussionsupporting
confidence: 92%
“…T 1 W silent imaging is a gradient-echo inversion recovery sequence, and recent studies have shown that when compared with T 1 W SE images, 3T T 1 W gradient-echo images depict a higher degree of myelination in both full-term neonates and term-equivalent age infants. 14 , 15 The results of our study are similar to those earlier reports; moreover, the use of an inversion recovery technique might have improved the T 1 contrast in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, most of the structures with increased T1w/T2w were involved with sensorimotor function. A diffusion study has reported higher values of fractional anisotropy (FA) in the right arcuate fasciculus in ME/CFS due to increase in myelination ( Tyan et al, 2015 , Sakuma et al, 1991 ) which is adjacent to the right ILF region reported here.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, T1w image data divided by T2w increases the WM to GM tissue contrast. Changes in tissue microstructure (myelin, iron, edema, and brain lesions) affect both T1w and T2w images and have been used separately to study myelination and iron in the human brain ( Tyan et al, 2015 , Bakshi et al, 2001 ). Whole brain T1w/T2w ratio maps have provided a sensitive measure, related to myelin and microstructural integrity in multiple sclerosis ( Beer et al, 2016 ) and schizophrenia ( Ganzetti et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional analyses of different sequence types (e.g., 2D and 3D) are ongoing to see if sequence type affects contrast improvement. Optimal pulse sequence parameters for the visualization of myelin in term neonates may vary with field strength, 35 and the value of the ratio technique at 3T remains to be determined. Finally, it may be possible to fully automate the processing pipeline, which could open the door for real-time assessment at the radiologist's workstation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses of different sequence types (e.g., 2D and 3D) are ongoing to see if sequence type affects contrast improvement. Optimal pulse sequence parameters for the visualization of myelin in term neonates may vary with field strength, and the value of the ratio technique at 3T remains to be determined.…”
Section: Discussionmentioning
confidence: 99%